Cortico-limbic disruption, material-specificity, and deficits in cognitive-affective theory of mind. Issue 2 (24th April 2023) - Singh, Varsha; Grewal, Kirat S; Vibha, Deepti; Singh, Rajesh K; Ramanujam, Bhargavi; Nehra, Ashima; Chandra, Sarat P; Gaikwad, Shailesh; Babu, Indupriya; Tripathi, Manjari
Abstract: The Theory of Mind deficit due to cognitive-affective disintegration is a poorly understood cognitive consequence of cortical and subcortical disruption in right temporal lobe epilepsy. Following Marr's trilevel approach, we used the material-specific processing model to understand the Theory of Mind deficit in drug-resistant epilepsy ( N = 30). We examined pre- and post-surgery changes in first-order (somatic-affective, non-verbal component) and second-order Theory of Mind (cognitive-verbal component) in three groups formed using: (i) seizure side (right versus left), (ii) right temporal epilepsy (right temporal lobe epilepsy versus non-right temporal lobe epilepsy), and (iii) right temporal lobe epilepsy with amygdalohippocampectomy (right temporal lobe epilepsy versus left temporal lobe epilepsy amygdalohippocampectomy versus non-amygdalohippocampectomy). We observed a marked deficit in the first-order Theory of Mind in the right temporal lobe amygdalohippocampectomy group; we mapped this deficit to decline in the non-verbal component of Theory of Mind (somatic-affective component). Preliminary results support using a material-specific processing model to understand the Theory of Mind deficits in right temporal lobe epilepsy amygdalohippocampectomy. Malleability of verbal processing in presence of deterioration of non-verbal processing might have clinical relevance for post-surgery recovery in right temporal lobe epilepsy amygdalohippocampectomy. Documenting the material-specific nature of deficits (verbal versus non-verbal) in non-western, linguistically, and socioeconomically diverse country enables us to understand the problem of heterogeneity in post-surgery cognitive consequences in the right amygdalohippocampectomy. Abstract : Post-surgery cognitive deficits in temporal lobe epilepsy are poorly understood; Singh et al . applied material-specific processing model to Theory of mind deficit and observed that cognitive-affective disintegration in right temporal epilepsy with cortico-limbic disruption (amygdalohippocampectomy) showed first order Theory of mind deficit, potentially due to material-specific alteration of non-verbal processing. Graphical Abstract: Graphical abstract